A consensus based vulnerability assessment to climate change in Germany. Issue 3 (17th August 2015) - Greiving, Stefan; Zebisch, Marc; Schneiderbauer, Stefan; Fleischhauer, Mark; Lindner, Christian; Lückenkötter, Johannes; Buth, Mareike; Kahlenborn, Walter; Schauser, Inke
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to propose a collaborative approach toward an integrated vulnerability assessment to climate change in Germany that attempts to bridge the gap between scientific output and policy demand. Design/methodology/approach – Conceptually, the approach follows the definition of vulnerability as used by the Intergovernmental Panel on Climate Change, but it has modified this basic concept. It clearly distinguishes between three time slices (presence, near and remote future) not only regarding the change in the climatic conditions but also socio-economic development trends. Findings – The paper concentrates on the selected methodological framework, the collaborative research design and those preliminary results of the nationwide vulnerability assessment that are transferable to other settings. Practical implications – A Vulnerability Network ("Netzwerk Vulnerabilitaet") emerged from an applied research project commissioned under the Adaptation Action Plan of the German Strategy for Adaptation to Climate Change by the Federal Ministry for the Environment, Nature Conservation, Building and Nuclear Safety and the Federal Environment Agency. The assessment serves as evidence basis for the implementation of the German Adaptation Strategy. Thus, all relevant federal authorities and agencies are represented in the Vulnerability Network. Originality/value – The approach is the first really integrative vulnerability assessment for the whole Germany, as it considers not only 16 sectors but also interconnections between these sectors and cumulative effects for three different time slices. Moreover, the normative component of the assessment was clearly separated from the analytic one. The Vulnerability Network as a whole has been responsible for all normative decisions to be taken during the assessment procedure thus ensuring a wide understanding and acceptance of commonly achieved results.